Correlates of poor self-rated health among school-going adolescent girls in urban Varanasi, India - Ratna Patel; Dhananjay W. Bansod (BMC, 2023)
Abstract Background The concept of self-rated health (SRH) has widely been studied among the adults and older population in developed as well as developing countries, including India. Also, studies are available in abundance examining the various concepts of SRH among adolescents. However, in India, studies on the SRH of adolescents remain scarce, especially those aiming to understand the correlates of SRH among school-going adolescent girls in an urban setting. Therefore, this study aims to determine the correlates of poor SRH among school-going adolescent girls in the urban setting of Varanasi, India. Methods This study is based on the primary data collected in the Varanasi district of Uttar Pradesh, India, from October 2019 to February 2020. Nearly 350 adolescent girls and their mothers were personally interviewed. Self-rated health was the primary outcome variable of this study. The exact wording of the question asked from the adolescent girls was, "In general, how would you say your health is?". Results Almost one-fifth (19.4%) of the adolescent girls reported poor SRH. Adolescent girls from Other Backward Class (OBC) [OR: 0.39; 95% CI: .18-.85] and Others caste [OR: 0.58; 95% CI: .23-0.87] were less likely to report poor SRH than their Scheduled Caste/Scheduled Tribe (SC/ST) counterparts. Girls residing in households where number of daughters were more than sons were more likely to report poor SRH [OR: 7.8; 95% CI: 1.5-39.5] than girls who belonged to the daughters only households. Conclusion Composition of children was one of the important factors as outlined in this study. The role of mothers in improving the overall SRH of the girls is critical as they are involved in caring process of their daughters.